Developing a Set of Learning Tools Based on Realistic Mathematics Education for Sequences and Series Assisted by MathCityMap in Islamic Boarding School - Hanifah Rizki Mubarokah; Didik Sugeng Pambudi; 3Nurcholif Diah Sri Lestari; Dian Kurniati; Abi Suwito (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
Mathematics learning is essential for strengthening students’ logical reasoning and numeracy skills, particularly in abstract topics such as sequences and series; however, instructional practices in Islamic boarding schools often remain procedural and insufficiently contextualized, creating a gap between theoretical recommendations of meaningful learning and classroom reality. This study aims to develop and evaluate RME-based learning tools for sequences and series assisted by MathCityMap to determine their validity, practicality, and effectiveness in a pesantren context. The research employed a 4D development model consisting of Define, Design, Develop, and Disseminate stages. Implementation involving an experimental class and a control class, each comprising 34 students. Data were collected through expert validation sheets, observation instruments, questionnaires, interviews, and numeracy pretest-posttest assessments. The results show that all learning tools achieved valid criteria, with average expert scores above 3.75 on a four-point scale. Practicality was confirmed by 95% implementation fidelity, 84.9% active student participation, and highly positive teacher and student responses. Effectiveness testing revealed a moderate N-gain score of 0.65 in the experimental class compared to 0.54 in the control class, with an independent samples t-test indicating a significant difference (Sig. = 0.049 < 0.05). These findings demonstrate that integrating Realistic Mathematics Education with MathCityMap enhances conceptual understanding, engagement, and numeracy achievement in sequences and series learning within Islamic boarding schools.